Facile synthesis of porous FeCo2O4 nanowire arrays on flexible carbon cloth with superior lithium storage properties. (November 2018) - Ni, Lianshan; Jia, Lulu; Chen, Gen; Wang, Fenglin; Liu, Xiaohe; Ma, Renzhi
Abstract: In this work, one-dimensional (1D) needle-like porous FeCo2 O4 nanowire arrays on flexible carbon cloth (CC) are successfully fabricated by a facile synthesis route and investigated as anode material for lithium ion batteries (LIBs). X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), and X-ray photoelectron spectroscopy (XPS) have been applied to characterize the materials. The 1D FeCo2 O4 nanowires provide a large surface area and enough space to accommodate volume changes. Besides, taking advantages of good conductivity from the CC substrate and the synergistic effect between Co and Fe ions, the integrated FeCo2 O4 nanowire arrays/CC electrodes exhibits prominent lithium-storage performance with high reversible capacity of about 2101 mAh g −1 at 100 mA g −1 and outstanding capacity retention of 97.1% from 2 to 200 cycles, and retains high rate capacity of 876 mAh g −1 at 2 A g −1 . Even cycled at higher current density of 1 A g −1, FeCo2 O4 nanowire arrays/CC electrode still maintains stable reversible capacity of 1013.8 mAh g −1 after 350 cycles, corresponding to 78.3% of the second discharge capacity. Therefore, FeCo2 O4 nanowire arrays/CC could be considered to be a promising candidate as anode material for flexible Li-ion batteries and future stretchable/bendable electronic devices. Graphical abstract: One-dimensional needle-like porous FeCo2 O4 nanowire arrays on flexible carbon cloth (CC) by a facile hydrothermal method and subsequent post-annealing treatment. FeCo2 O4 nanowire arrays/CC exhibits outstanding lithium storage performance in terms of high reversible capacity, good cycling stability, and superior rate capability, which can be considered to be a promising candidate as anode material for flexible Li-ion batteries and future stretchable/bendable electronic devices. Image 1 Highlights: FeCo2 O4 nanowires/CC were synthesized via a facile hydrothermal reaction followed by annealing treatment. FeCo2 O4 nanowires/CC showed high capacity, superior capacity retention, and outstanding rate performance. FeCo2 O4 nanowires/CC could be applied to the flexible Li-ion batteries and wearable devices.